The Influence Of Peer Group Support On Knowledge And Personal Hygiene Attitudes During Menstruation In Adolescent Girls At Smp Negeri 2 Tumpang, Malang District - Eri Puji Kumalasari; Imawati; Devy Putri Nursanti; Miftakhur Rohmah; Asasih Villasari (Universitas STRADA Indonesia, 2025)
Prevention of poor menstrual hygiene practices in adolescent girls can be done through behavioral change interventions starting from providing guidelines, management, developing communication media, information and education. The research design used in this study was the Pre-experimental method with a one group pretest posttest design and the sample in this study was adolescent girls with a sample size of 80 respondents at SMP N 2 Tumpang, the sampling method in this study used the simple random sampling technique. There is a significant influence between before peer group support and after peer group support on the knowledge of adolescent girls at SMP N 2 Tumpang with the results of statistical tests obtained a value of p = 0.000.